Character Education Management Based on Sumang Local Wisdom: Insights from Madrasah Aliyah Negeri 1 Central Aceh - Raudatussaadah; Mesiono; Mahariah (Tadbir : Jurnal Studi Manajemen Pendidikan, 2026)
This study aims to describe and analyze the planning, implementation, supervision, and effectiveness of character education through Sumang local wisdom values of Sumang culture at Madrasah Aliyah Negeri 1 Central Aceh, as well as the effectiveness of character education through the local wisdom values of Sumang culture at Madrasah Aliyah Negeri 1 Central Aceh. The research method used in this study employs a qualitative approach with a descriptive analysis research type. The data collection methods used in this study include participatory observation, interviews, observation, and documents, records, or archives. The data sources in this study are divided into two categories: primary data and secondary data. The primary data was collected from the school principal, the vice principal in charge of curriculum, school teachers, school staff, the committee, and 3 students. The results of the study reveal that the planning of character education through the local wisdom values of Sumang culture at Madrasah Aliyah Negeri 1 Central Aceh is carried out through a curriculum that is aligned with the Merdeka Curriculum. The implementation is conducted through the integration of character values into the subjects of Akidah Akhlak and Citizenship Education. Subsequently, supervision is carried out by compiling reports in the form of personal books on examination implementation and students’ learning outcomes or report cards. In this regard, the effectiveness of the implementation of character education through the local wisdom values of Sumang culture at Madrasah Aliyah Negeri 1 Central Aceh is in accordance with the madrasah’s vision, a well-directed learning process, and changes in students’ behavior.